2016
DOI: 10.1007/s11882-016-0657-y
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Respiratory Allergic Diseases in Healthcare Workers

Abstract: Healthcare workers (HCWs) are exposed to a range of high and low molecular weight agents that are allergic sensitizers or irritants including cleaners and disinfectants, natural rubber latex, and various medications. Studies have shown that exposed HCWs are at risk for work-related rhinitis and asthma (WRA). Work-related rhinitis may precede development of WRA and should be considered as an early marker of WRA. Avoidance of causative exposures through control strategies such as elimination, substitution, engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 83 publications
0
10
0
4
Order By: Relevance
“…Work-related asthma (WRA) subsumes occupational asthma and work-exacerbated asthma, and is a common but preventable respiratory disease occurring in the workplace (Friedman-Jimenez et al, 2015;Tarlo et al, 2008). In 2016, WRA affected as many as 2.7 million U.S. workers, especially healthcare workers who had among the highest prevalence of current and lifetime asthma (10.7-12.4%) (Dodd and Mazurek, 2016;Mazurek and Weissman, 2016;Wiszniewska and Walusiak-Skorupa, 2014). Asthma is a heterogeneous disease characterized by chronic airway inflammation, with variable airflow limitation and symptoms such as wheeze, chest tightness, frequent cough, and shortness of breath (SOB) (Global Initiative for Asthma, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work-related asthma (WRA) subsumes occupational asthma and work-exacerbated asthma, and is a common but preventable respiratory disease occurring in the workplace (Friedman-Jimenez et al, 2015;Tarlo et al, 2008). In 2016, WRA affected as many as 2.7 million U.S. workers, especially healthcare workers who had among the highest prevalence of current and lifetime asthma (10.7-12.4%) (Dodd and Mazurek, 2016;Mazurek and Weissman, 2016;Wiszniewska and Walusiak-Skorupa, 2014). Asthma is a heterogeneous disease characterized by chronic airway inflammation, with variable airflow limitation and symptoms such as wheeze, chest tightness, frequent cough, and shortness of breath (SOB) (Global Initiative for Asthma, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reviews of epidemiologic studies have identified cleaning and disinfecting activities (CDAs) as important risk factors for asthma-related outcomes among healthcare workers (Folletti et al, 2017;Mazurek and Weissman, 2016;Wiszniewska and Walusiak-Skorupa, 2014;Zock et al, 2010). However, the complexity of CDAs and the exposures they generate in healthcare settings has rarely been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Asma terkait pekerjaan meliputi asma kerja (occupational asthma) dan asma yang diperburuk oleh faktor pekerjaan (work-exacerbated asthma). 1 Diantara penderita asma dewasa yang ada saat ini, diperkirakan 9% diantaranya adalah tena-ga kesehatan yang mengalami asma terkait kerja.…”
Section: Pendahuluanunclassified
“…Sebanyak 42,3% dari penderita asma tersebut terkait pekerjaannya di sarana kesehatan secara umum dan 40,2% lainnya terkait dengan pekerjaanya di rumah sakit. 1…”
Section: Pendahuluanunclassified
See 1 more Smart Citation